2023
DOI: 10.3390/agronomy13061499
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Detectability of Corn Smut Fungus (Ustilago maydis DC. Corda) Infection Based on UAV Multispectral Technology

Abstract: Corn smut fungus (Ustilago maydis [DC.] Corda) is a globally widespread pathogen affecting both forage and sweet maize hybrids, with higher significance in sweet maize. Remote sensing technologies demonstrated favorable results for disease monitoring on the field scale. The study focused on the changes in vegetation index (VI) values influenced by the pathogen. In this study, four hybrids, two forage maize and two sweet maize hybrids were examined. Artificial infection was carried out at three different doses:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Nevertheless, the degree of infection is also influenced by hybrid resistance to specific pathogens. The research conducted in Hungary indicated that common smut infection exhibits divergent effects on various maize hybrids, particularly emphasizing the higher impact on sweet maize hybrids [ 10 ]. Therefore, developing hybrids that are resistant to pathogens through breeding or genetic engineering is crucial to establishing a foundation for sustainable agriculture [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the degree of infection is also influenced by hybrid resistance to specific pathogens. The research conducted in Hungary indicated that common smut infection exhibits divergent effects on various maize hybrids, particularly emphasizing the higher impact on sweet maize hybrids [ 10 ]. Therefore, developing hybrids that are resistant to pathogens through breeding or genetic engineering is crucial to establishing a foundation for sustainable agriculture [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from researchers in China suggest that the resistance to maize common smut may be attributed to intricate gene co-expression and metabolism networks associated with amino acids and reactive oxygen species metabolism [ 10 ]. German research demonstrates that breeding or engineering maize hybrids with enhanced resistance, specifically targeting the susceptibility factor lipoxygenase 3 through gene-editing techniques, holds promise for reducing disease symptoms and fungal infections caused by U. maydis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation